The Relationship Between Work-Life Balance And Turnover Intention Among Employees In The Public University - Alya Syahirah, Zainul Abidin (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study was conducted to determine the relationship between work-life balance (schedule flexibility, manager support and job autonomy) and turnover intention among employees in the public university. This research was done by using a quantitative method where the questionnaire was used to collect the data. Descriptive statistics and inferential statistics were used to ease understanding. As 113 samples from one of the public universities in Malaysia collected for this study. Besides, SPSS version 20.0 was used to analyze the collected data. Pearson Correlation test was used to identify the relationship between the independent variable and the dependent variable. The findings have shown that there is a significant relationship between schedule flexibility and turnover intention. Furthermore, there is a significant relationship between manager support and turnover intention. Besides, it was also found that there is a significant relationship between job autonomy and turnover intention.